BEAST: A model for the assessment of system-wide risks and macroprudential policies - Katarzyna Budnik; Johannes Groß; Gianluca Vagliano; Ivan Dimitrov; Max Lampe; Jiri Panos; Sofia Velasco; Louis Boucherie; Martina Jancoková (European Central Bank (ECB), 2023)
The Banking Euro Area Stress Test (BEAST) is a large-scale semi-structural model developed to analyse the euro area banking system from a macroprudential perspective. The model combines the dynamics of approximately 90 of the largest euro area banks with those of individual euro area economies. It reflects the heterogeneity of banks by replicating the structure of their balance sheets and profit and loss accounts. Additionally, it allows banks to adjust their assets, funding mix, pricing decisions, management buffers, and profit distribution along with individual bank conditions, including their capital and liquidity requirements, and other supervisory limits. The responses of banks impact credit supply conditions and have feedback effects on the macroeconomic environment. Stochastic solutions of the model provide a solid foundation for investigating multiple scenarios, deriving at-risk measures, and estimating model uncertainty. The model is regularly utilised to assess the resilience of the euro area banking sector, including in the biennial ECB macroprudential stress tests, as well as to analyse the effects of regulatory, macroprudential, and monetary policy changes.
Keywords: E37; E58; G21; G28; 330; macro stress test; macroprudential policy; banking sector deleveraging; real economy-financial sector feedback loop